Pengaruh Keselamatan Kerja Lingkungan Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan CV. Elraya Group - Riska Fauziah; Indah Yuni Astuti; Agung Pambudi Mahaputra (Jurnal Ekonomi dan Manajemen, 2022)
This research was motivated by the achievement of work targets that have not been perfect. It showed that the employee's performance was not optimal in completing the work. In this case the authors found indications of work safety, work environment and work discipline that were still not good, such as employees who did not use PPE when they were working, cleanliness was not maintained and there were employees who were late and went to home early. The aim of this study was to explain the significant influence between work safety, work environment and work discipline on the performance of employees of CV. Elraya Group. The sample of this study was the entire population of 59 respondents using the sampling method that was saturated sampling. The data analysis technique used in this research was validity and reliability test, classical assumption test, multiple linear regression test and hypothesis testing. Overall, it can be explained that work safety (partial) had a significant effect on employee performance (sig. t value 0.036 <0.05). The work environment (partial) had a significant effect on employee performance (sig. t value 0.029 <0.05). Work discipline (partial) had a significant effect on employee performance (sig. t value 0.013 <0.05). Work safety, work environment and work discipline (simultaneously) had a significant effect on employee performance (sig. F value 0.00 <0.05). The coefficient of determination (R2) was 0.345 which indicated that employee's performance was influenced by the variables of work safety, work environment and work discipline by 34.5%, the remaining 65.5% was influenced by other variables.